THE (IN)EFFECTIVENESS OF FAMILY MEDIATION TO THE PROTECTION OF CHILD AND ADOLESCENT PERSONALITY RIGHTS: THE (IN)EFFECTIVENESS OF FAMILY MEDIATION TO THE PROTECTION OF CHILD AND ADOLESCENT PERSONALITY RIGHTS (Revista Direito em Debate, 2021)
This article analyzes the personality rights of children and adolescents who are mediated by their parents, studying the judicial conjuncture and the method of mediation applied in this scenario. Using the hypothetical-deductive method, the article assumes that the current mediation configuration ends up violating personality rights rather than actually make it effective. To prove this hypothesis, the qualitative criterion and the bibliographic research technique were used. The research revealed the distortion of family mediation in Brazil, as well as its inadequate application in conflicts. It was also verified that the rights of the personality of children are injured with such scenario, being a change aimed at the resolution of family conflicts urgent, that because of its special nature, tends to involve existential and immaterial issues, marked by feelings and anxiety. Thus, this article warns of an evil that plagues the Family Law, while explain the importance of the personality rights for human development, especially of children and adolescents.
Keywords: Conflict; Human Dignity; Personality Rights; Mediation; Civil Procedure.